Vitamin B6 and Cancer Risk: A Field Synopsis and Meta-Analysis. (31st October 2016) - Mocellin, Simone; Briarava, Marta; Pilati, Pierluigi
Abstract: Background : Vitamin B6 is involved in many biochemical reactions and might play a role in carcinogenesis. We summarized the evidence linking vitamin B6 to cancer risk. Methods: We conducted a systematic review of both observational and intervention studies investigating the relationship between vitamin B6 intake or blood levels of its bioactive form pyridoxal-5'-phosphate (PLP) and the risk of any type of cancer. Random-effects meta-analysis was used to calculate pooled relative risks (RRs) and their 95% confidence intervals (CIs) across studies for high vs low categories of vitamin intake or PLP levels. We also performed a random-effects dose-response meta-analysis. Results: We identified 121 observational studies (participants, n = 1 924 506; cases, n = 96, 436) and nine randomized controlled trials (RCTs; participants, n = 34 911; cases, n = 2539) considering 19 tumor sites. High intake of dietary (food only) vitamin B6 was statistically significantly associated with lower risk of all cancers (relative risk [RR] = 0.78, 95% CI = 0.73 to 0.84) and specific tumors, with special regard to gastrointestinal carcinomas (RR = 0.68, 95% CI = 0.61 to 0.75). An inverse association was also observed between high PLP levels and the risk of all cancers (RR = 0.66, 95% CI = 0.58 to 0.76) and single tumor sites, the most consistent results being those for gastrointestinal tumors (RR = 0.56, 95% CI = 0.48 to 0.65). There was a statistically significant inverse linear relationship between cancer risk and both vitamin B6 dietary intake and PLP levels. When total (food and supplements) intake was considered, the associations were weaker or null. Findings from RCTs did not support a protective effect of vitamin B6 against cancer, although this evidence was graded as low level. Conclusions: Epidemiological evidence supports the potential of vitamin B6 as a cancer risk reduction agent and the role of PLP as a cancer screening biomarker, especially for gastrointestinal tumors. However, inconsistent findings from total intake and intervention studies suggest that vitamin B6 might also be an indicator of other dietary protective micronutrients.